Refractory pyoderma gangrenosum treated with infliximab in an infant. (April 2014) - Campos‐Muñoz, L.; Conde‐Taboada, A.; Aleo, E.; Toledano, E.; López‐Bran, E.
Summary We report the case of an 11‐month‐old boy with severe recalcitrant pyoderma gangrenosum refractory to prednisone, dapsone and ciclosporin. Treatment with infliximab was well tolerated, and resulted in an excellent clinical response that has been sustained for 15 months. The characteristics of this condition in children and the use of infliximab in infants are both reviewed.